Genome-wide association study identifies genetic risk underlying primary rhegmatogenous retinal detachment. - Kirin, M; Chandra, A; Charteris, D; Hayward, C; Campbell, S; Celap, I; Bencic, G; Vatavuk, Z; Kirac, I; Richards, A; Tenesa, A; Snead, M; et al. (2013)
Rhegmatogenous retinal detachment (RRD) is an important cause of vision loss and can potentially lead to blindness. The underlying pathogenesis is complex and incompletely understood. We applied a two-stage genetic association discovery phase followed by a replication phase in a combined total of 2833 RRD cases and 7871 controls. The discovery phase involved a genome-wide association scan of 867 affected individuals and 1953 controls from Scotland, followed by genotyping and testing 4347 highest ranking or candidate single nucleotide polymorphisms (SNPs) in independent sets of cases (1000) and controls (2912) of Dutch and British origin. None of the SNPs selected reached a Bonferroni-corrected threshold for significance (P < 1.27 × 10(-7)). The strongest association, for rs12960119 (P = 1.58 × 10(-7)) located within an intron of the SS18 gene. Further testing was carried out in independent case-control series from London (846 cases) and Croatia (120 cases). The combined meta-analysis identified one association reaching genome-wide significance for rs267738 (OR = 1.29, P = 2.11 × 10(-8)), a missense coding SNP and eQTL for CERS2 encoding the protein ceramide synthase 2. Several of the top signals showing suggestive significance in the combined meta-analysis encompassed genes with a documented role in cell adhesion or migration, including SS18, TIAM1, TSTA3 and LDB2, which warrant further investigation. This first genetic association study of RRD supports a polygenic component underlying RRD risk since 27.4% of the underlying RRD liability could be explained by the collective additive effects of the genotyped SNP from the discovery genome-wide scan.